2017
DOI: 10.1111/xen.12375
|View full text |Cite
|
Sign up to set email alerts
|

Examining the potential for porcine‐derived islet cells to harbour viral pathogens

Abstract: With an onus on safety in the potential use of porcine islet cells as a treatment for diabetes, the use of animals lacking exogenous pathogens is clearly important and multilevel screening strategies have been presented on testing animals and the product. In this study, we wished to investigate whether islet cells indeed harboured the same viral pathogens of concern in the source animal. PMBC and islet cells from both adult and neonatal source animals were directly compared and tested for PCMV, PLHV, PCV2, PPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Indeed, it has also been suggested that islets may not harbour many of the viral pathogens identified in the donor pig. 17 However, we recognize that this study was conducted for a relatively short time period of 8 weeks and that a longer study would be valuable in examining this further. Although, it should be noted that PK15 cells used in this study are high PERV producers and it is likely a lower barrier of protection is required to protect as against PERV transmission from islet cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has also been suggested that islets may not harbour many of the viral pathogens identified in the donor pig. 17 However, we recognize that this study was conducted for a relatively short time period of 8 weeks and that a longer study would be valuable in examining this further. Although, it should be noted that PK15 cells used in this study are high PERV producers and it is likely a lower barrier of protection is required to protect as against PERV transmission from islet cells.…”
Section: Discussionmentioning
confidence: 99%
“…In general, ssDNA viruses infecting humans and pigs are widely prevalent and have high mutation rates. However, this high prevalence may not hinder the use of pig xenografts, as a recent report highlights that islet cells of pigs do not carry common pig viruses including PCV2 and PPV1, even if other cells such as PBMCs carry them . Indeed, xenotransplantation of islet cells from pigs to cynomolgus monkeys in preclinical trials and from pigs to human patients in clinical trials has been achieved without transmission of any pig viruses including ssDNA viruses such as PPV, PCV1, and PCV2 .…”
Section: Discussionmentioning
confidence: 99%
“…Careful husbandry and rigorous screening are critical to exclude pathogenic microorganisms from the donor pig herd . Interestingly, in the case of islets, the product may be “clean” even if the herd is “dirty.” Crossan et al isolated islets from pigs which had tested positive for one or more of five potentially zoonotic viruses in serum or peripheral blood mononuclear cells. All of the islet preparations were found to be negative for all viruses tested.…”
Section: Progress Towards Minimizing Microbiological Risksmentioning
confidence: 99%